2004
DOI: 10.1042/bst0320575
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the DST-mediated mRNA decay pathway using a transgene-based selection

Abstract: mRNA sequences that control abundance, localization and translation initiation have been identified, yet the factors that recognize these sequences are largely unknown. In this report, a transgene-based strategy designed to isolate mutants of Arabidopsis thaliana that fail to recognize these sequences is described. In this strategy, a selectable gene and a screenable marker gene are put under the control of the sequence element being analysed and mutants are selected with altered abundance of the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…AtFER1 mRNA stability was also studied in two trans ‐acting mutants, named dst1 and dst2 , previously identified in a genetic screen aimed at isolating factors involved in the DST‐dependent mRNA degradation pathway (Johnson et al , 2000; Pérez‐Amador et al , 2001; Lidder et al , 2004). AtFER1 mRNA accumulation in response to Fe was measured in Col, dst1 and dst2 grown in liquid medium (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AtFER1 mRNA stability was also studied in two trans ‐acting mutants, named dst1 and dst2 , previously identified in a genetic screen aimed at isolating factors involved in the DST‐dependent mRNA degradation pathway (Johnson et al , 2000; Pérez‐Amador et al , 2001; Lidder et al , 2004). AtFER1 mRNA accumulation in response to Fe was measured in Col, dst1 and dst2 grown in liquid medium (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…A genome‐wide study in Arabidopsis showed that the DST sequence was enriched in unstable transcripts (Narsai et al , 2007). Three trans ‐acting components of the DST pathway, named DST1–3, were isolated by a forward genetic approach (Johnson et al , 2000; Pérez‐Amador et al , 2001; Lidder et al , 2004). Molecular and phenotypic analysis of the dst mutants showed deregulation of functional subsets of genes including some circadian clock‐related genes (Pérez‐Amador et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For several circadian genes, a specific post-transcriptional mRNA decay mechanism has been postulated [34]. The circadian control of messenger stability was found to be associated to a sequence specific decay pathway [34,35]. Instability determinants of clock controlled mRNAs might be located within untranslated regions, introns or within the coding region as shown for mRNA of CIR-CADIAN CLOCK ASSOCIATED 1 (CCA1) [36].…”
Section: Transcriptional Control Of Sut1 Post-transcriptional Contromentioning
confidence: 99%